AL-TABARSI TOKOH TAFSIR KLASIK SYIAH MODERAT (468-548 H) Telaah atas kitab Majma’ al-Bayan fi Tafsir al-Qur’an - Ali Aljufri dan Mufidah Aljufri (Program Studi Ilmu Al-Qur'an dan Tafsir, Institut Agama Islam Negeri (IAIN) Palu, 2021)
The Qur’an is the first source of law in Islam so it has received great attention from various circles. Many works have emerged inspired by the Qur'an from both Sunnis and Shiites. One of the monumental Shiite works that appeared in the 6th century AH was the book tafsir Majma 'al-Bayân fi Tafsir al-Qur'ân written by al-Fadhl ibn al-Hasan ibn al-Fadhl al-Tabarsi (d.548 AH ). Tafsir among the Ja'fariyah Shiites is quite moderate. Since his youth, he has had an obsession and ambition to write a book on the interpretation of the Qur'an. This obsession manifested itself in the year 534 H when he was 66 years old. Al-Thabarsi is a Shiite scholar who has many talents. That can be seen from his manhaj in interpreting the Qur'an. He discusses the issue of the number of verses, differences of opinion around it, the priority of the letter, differences in reading and reasons, i'rab, linguistic studies, asbab al-nuzul, the meaning of verses, and correlation, he describes the problem in various aspects well.